Analisis Pengembangan Home Industri Kerajinan Purun di Kelurahan Palam Kecamatan Cempaka, Kota Banjarbaru - Liyanawati, Irma; Rizali (PPJP ULM, 2019)
This study aims to determine the relationship of aspects of working capital,raw materials, labor, and marketing to the purun home industry's development.Respondents interviewed ten artisans with data collection techniques through theinterview, observation, and documentation. The data analysis technique used isdescriptive. Namely, the data presented in tabulation form and the percentage of eachanswer category are calculated and to determine the existence of independentvariables, both free and bound, without linking the relationship between thesevariables.This study shows that limited aspects of capital and unskilled labor influencethe purun craft home industry's development. The difficulty of capital lendingrequirements from related parties makes it difficult for artisans to manage it and theimbalance of skills among artisans hinders the production process.